2022
DOI: 10.3390/cancers14030764
|View full text |Cite
|
Sign up to set email alerts
|

BKV Related Hemorrhagic Cystitis—An Insight into Risk Factors and Later Complications—An Analysis on Behalf of Polish Adult Leukemia Group

Abstract: BK virus reactivation increases the likelihood of hemorrhagic cystitis (HC) after allogeneic hematopoietic stem cell transplant (HCT). In this study, we aimed to identify predictive and risk factors associated with the increased occurrence of this condition following HCT. On a group of 124 patients aged ≤71 years old (median 40 years) who underwent HCT, we analyzed sex, age, time from diagnosis to transplantation, type of conditioning, donor’s relationship, age, and sex, the impact of immunosuppression with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
3
5
0
1
Order By: Relevance
“…Subsequently, two reviewers (Zhou and Fan) screened the title/abstract of the remaining studies; 1549 studies were excluded as they were unrelated to risk factors for BKV‐HC. The full texts of the remaining 99 studies were further reviewed; of these, 11 studies met the inclusion and exclusion criteria and were included in this meta‐analysis 15–25 . All included studies were retrospective and published between 2013 and 2022.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, two reviewers (Zhou and Fan) screened the title/abstract of the remaining studies; 1549 studies were excluded as they were unrelated to risk factors for BKV‐HC. The full texts of the remaining 99 studies were further reviewed; of these, 11 studies met the inclusion and exclusion criteria and were included in this meta‐analysis 15–25 . All included studies were retrospective and published between 2013 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several studies have reported risk factors for BKV-HC, such as cord blood transplantation, myeloablative conditioning, graft-versus-host-disease, and use of cyclophosphamide and busulfan. [15][16][17][18][19][20][21][22][23][24][25] The conclusions of previous studies were disparate, which could be attributed to the fact that the patients were from different regions of the world. The risk factors for BKV-HC remain debatable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cesaro et al (2018) relatou uma resposta de 83% em um estudo com 35 pacientes, assim como os locais de sangramento são cauterizados e colocados cola de fibrina nas partes lesadas da mucosa, através de intervenções endoscópicas, porém complicações possíveis são a obstrução dos ereteres. A cistectomia é referida como sendo o último recurso para os casos de cistite hemorrágica refratária, sendo feita a nível parcial para a preservação da uretra e colo vesical, dando possibilidade a uma capaz reconstrução cirúrgica futura (Dybko et al, 2022).…”
Section: Silva M J S D (2018)unclassified